실리콘 웨이퍼의 그리비지 다이싱 역학 - 이성민; Seong-min Lee; 김연욱; Yeon-wook Kim (대한금속·재료학회지, 57(11), 2019)
This article details how effectively dicing damage of silicon wafers can be mechanically minimized by appropriate laser-induced groove formation prior to wafer separation. Various laser dicing factors, such as the laser-control power, the scan rate and the scan number of the laser beam, were estimated to determine the optimum groove morphology for minimization of chipping damage. The experimental results show that repeated low-power laser beam scanning can be more effective for proper groove formation than single highpower laser beam scanning. In-situ scanning electron microscopic examinations show that the curvature of a laser-induced groove tip can be the most critical factor for minimizing chipping damage during silicon wafer separation. The suppression of dicing damage on a silicon wafer with a sharp laser-induced tip can be explained by atomic force microscopic examinations showing that cleavage fractures along a {011}-crystal plane can be more possible at smaller curvature radius of the laser-induced groove. (Received June 26, 2019; Accepted August 30, 2019)